2017
DOI: 10.1021/acs.jpcb.7b01736
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Conformational Dynamics of Apo-Adenylate Kinase through a π–Cation Interaction

Abstract: Large-scale conformational transition from open to closed state of adenylate kinase (ADK) is essential for its catalytic cycle. Apo-ADK undergoes conformational transition in a way that closely resembles an open-to-closed conformational transition. Here, equilibrium simulations, free-energy simulations, and quantum mechanics/molecular mechanics (QM/MM) calculations in combination with several bioinformatics approaches have been used to explore the molecular origin of this conformational transition in apo-ADK. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Since folding/unfolding of a protein is a long time scale process, free energy simulations are generally preferred to explore the conformational landscape of protein. [96][97][98][99] During unfolding of a protein, the hydrophobic contacts which were present in the native state of the protein, disrupts. As a consequence of this, one often encounters structural changes in protein.…”
Section: Free Energy Landscape Of Hp-36 In Water and In Water-ethanol...mentioning
confidence: 99%
“…Since folding/unfolding of a protein is a long time scale process, free energy simulations are generally preferred to explore the conformational landscape of protein. [96][97][98][99] During unfolding of a protein, the hydrophobic contacts which were present in the native state of the protein, disrupts. As a consequence of this, one often encounters structural changes in protein.…”
Section: Free Energy Landscape Of Hp-36 In Water and In Water-ethanol...mentioning
confidence: 99%
“…Previously, we have also shown that the cation−π interaction is crucial for the conformational transition of apo adenylate kinase . Such interactions are often found to play an anchoring role in lipid specific recognition of membrane proteins .…”
Section: Resultsmentioning
confidence: 99%
“…54 Previously, we have also shown that the cation−π interaction is crucial for the conformational transition of apo adenylate kinase. 55 Such interactions are often found to play an anchoring role in lipid specific recognition of membrane proteins. 56 In cation−π interactions, the π-electron cloud interacts with the cationic part inside the same molecule or different molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, LYS57 is on the external part of NMP and has been identified to play a pivotal role in collaboration with ARG88 to block the release of adenine from the hydrophobic pocket of the protein . More generally, this amino acid is crucial for stabilizing the closed conformation of the kinase, , which was never observed throughout the simulation. The overall probability pattern persists as N increases, even though it is less pronounced.…”
Section: Resultsmentioning
confidence: 99%